Tourism and Gender-Based Violence: Challenging Inequalities 2020
DOI: 10.1079/9781789243215.0001
|View full text |Cite
|
Sign up to set email alerts
|

Introducing critical debates on gender-based violence in tourism.

Abstract: Please read the manuscript carefully, checking for accuracy, verifying the reference order and double-checking figures and tables.During the preparation of your manuscript for publication, the questions listed below have arisen. Please attend to these matters and return the answers to these questions when you return your corrections.Please note, we will not be able to proceed with your article and publish it in print if these queries have not been addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, the emic perspective and author-researcher involvement suggests a subjective influence on the interpretation of data. However, the relevance of subjective personal introspective insights is also acknowledged (Holbrook 2005, 2021; Stephens 2020), and my experiences as a babymoon traveler, and my knowledge and perspectives in autoethnography and netnography, shape the interpretations, that is, go beyond what is in the data itself (Kozinets 2020). Second, this article does not encompass all cultural spheres, as it takes a female Western middleclass perspective, which has influenced the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the emic perspective and author-researcher involvement suggests a subjective influence on the interpretation of data. However, the relevance of subjective personal introspective insights is also acknowledged (Holbrook 2005, 2021; Stephens 2020), and my experiences as a babymoon traveler, and my knowledge and perspectives in autoethnography and netnography, shape the interpretations, that is, go beyond what is in the data itself (Kozinets 2020). Second, this article does not encompass all cultural spheres, as it takes a female Western middleclass perspective, which has influenced the data.…”
Section: Discussionmentioning
confidence: 99%
“…The method is not mainstream in tourism and business research (Buckley 2012), perhaps due to reluctance by researchers to reveal personal experiences (Bell, Bryman, and Harley 2019). Nevertheless, autoethnography is an emergent approach in tourism (Beeton 2022; Buzinde 2020; Houge Mackenzie and Kerr 2013; Kuuru 2022; Noy 2008; Scarles 2010; Shepherd, Laven, and Shamma 2020), which allows for understanding one’s own subjectivity and the way in which we relate to those we encounter (Stephens 2020), and was therefore considered appropriate for this study as it allowed for an insider perspective on babymoon tourism, providing rich data about the experience of a mother-to-be.…”
Section: Methodsmentioning
confidence: 99%
“…Gender is often absent, silenced or sidelined in mainstream discussions. For example, Eger et al (2020) highlighted the neglect of gender-based violence in dominant tourism discussions. Baum et al (2016) noted the limited attention paid to workforce considerations and related gender issues in the sustainable tourism literature.…”
Section: Troubling Tourism Sustainabilitymentioning
confidence: 99%
“…An example of such research can be found in the work of Vizcaino et al (2020), who, in drawing upon critical discourses of postcolonial feminism, shed light on the complexities of gender-based violence in the tourism arena. The authors highlight that sexual and gender-based harassment in tourism and hospitality are often invisible, routinised and, thus, normalised (Eger et al, 2020). Such silent harassment, which may entail sexual attention, coercion or hostility (Fitzgerald and Shullman, 1993), may happen not only with female tourists (Yang et al, 2020), but also in the tourism workplace (Alrawadieh and Demiderlen Alrawadieh, 2020; Turkoglu, 2020) and even within tourism academia (Finniear et al, 2020).…”
Section: Introductionmentioning
confidence: 99%